Pendampingan Penginputan Data pada Aplikasi e-Office Desa dalam Pengajuan Anggaran di Desa Jayamandiri, Kecamatan Cibugel, Kabupaten Sumedang - Ismi Dhini Saefa; Tumija Tumija; Dhimas Widya Saputra; Apriediya Pradigma Sirestu (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2023)
Jayamandiri Village is one of the villages in Cibugel District, Sumedang Regency which has used the E-Office application to support activities at the village office This application is an application issued by Sumedang Regency since 2020. However, in the implementation of this application it is known that Jayamandiri Village has proven not to be active in using the E-Office application, especially one of its features, namely SIMEDOK for budget submissions, which is the cause of the problem, namely the low the quality of the human resources of the Jayamandiri Village apparatus, the lack of facilities and infrastructure to support the application of the village E-Office so that its use is hampered furthermore there is no firm notification or firm appeal from the Cibugel District for the application of this application This community service uses direct observation and interview methods, the method used is in the form of implementation stages in community service which starts from the first stage, namely preparation related to problem identification The second stage is assistance in the application and input of E-Office data and the third stage is socialization which is carried out to increase understanding with the target of village officials, community leaders and the Jayamandiri Village community . The community service which was carried out for 10 days was also followed by writers who took part in a series of activities in the Jayamandiri Village community to find out more about the customs of the local community and related. The results of the assistance are that first the Jayamandiri Village apparatus understands the use of the E-Office application, especially the SIMEDOK feature for budget submissions. Second, the Jayamandiri Village apparatus applies the E-Office independently and performs all village office administration. Third, the use of the Village E-Office application can be felt by the output not only by Jayamandiri Village officials but also by the Village community, especially in public services.